Savoring Sundanese food: A discourse analysis of Instagrams powerful promotion of Bandungs culture and culinary - Rosaria Mita Amalia; Eva Tuckyta Sari Sujatna; Ekaning Krisnawati; Kasno Pamungkas (Universitas Syiah Kuala, 2024)
Department of Culture and Tourism in Bandung harnesses the power of its official Instagram account, @disbudpar.bdg, to promote the citys diverse tourist attractions and cultural richness. This study conducts an in-depth analysis of the various topics presented on the account that showcase the multifaceted nature of Sundanese culinary traditions. The researchers collected culinary information from 642 posts on Instagram feeds, resulting in 118 data points considering various cuisines, both traditional and modern. The focus of this study is on 86 data points related to traditional meals and beverages in 2022. Employing van Dijks Critical Discourse Analysis within the micro-structure theory, the descriptive qualitative method was used for the analysis. The findings reveal four distinct classifications of topics related to culinary diversity. They are the diversity of traditional Sundanese meals (66 data), the diversity of traditional Sundanese beverages (2 data), restaurants offering traditional foods and beverages (16 data), and ingredients for traditional pastries (2 data). Additionally, the analysis uncovers the use of interrogative sentences, declarative sentences, and lexical choices that effectively support and describe the promotion of culinary diversity as a prominent tourist attraction in Bandung. Interrogative sentences engaged followers, declarative sentences provided factual insights, and diverse lexical choices enticed readers to appreciate Bandungs culinary offerings.